Lisa in London - Victor, Paul. (Essex : Penguin, 2000)
It s Lisa s first trip to London. She s going to learn English. But on that first day in Delmore Street, something unexpected happens, and it s going to change her life!
Beginner.
Keywords: Readers; English language -- Study and teaching; Stage books